2018
DOI: 10.1016/j.devcel.2018.06.022
|View full text |Cite
|
Sign up to set email alerts
|

A lncRNA-like Role for LINE1s in Development

Abstract: Transposable elements (TEs) have profoundly affected the evolution of transcriptional and chromatin profiles in mammalian genomes. In a recent paper, Percharde et al. (2018) identify a lncRNA-like function for LINE1 transposable elements in regulating gene expression to facilitate embryonic stem cell self-renewal and preimplantation development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 10 publications
0
11
0
9
Order By: Relevance
“…More recently, using antisense oligonucleotides to deplete L1 transcripts, Percharde et al [126,127] presented evidence that LINE1 expression plays a role in mouse embryonic exit from the 2-cell stage by recruiting nucleolin and Kap1 to repress the master transcriptional regulator Dux and activate rRNA synthesis. Furthermore, Jachowicz et al [128] reported that LINE-1 activation after fertilization regulates global chromatin accessibility, and that artificial prolongation of L1 transcription in mouse embryos interferes with their development.…”
Section: A Possible Role For Misregulation Of Retrotransposon Expressmentioning
confidence: 99%
“…More recently, using antisense oligonucleotides to deplete L1 transcripts, Percharde et al [126,127] presented evidence that LINE1 expression plays a role in mouse embryonic exit from the 2-cell stage by recruiting nucleolin and Kap1 to repress the master transcriptional regulator Dux and activate rRNA synthesis. Furthermore, Jachowicz et al [128] reported that LINE-1 activation after fertilization regulates global chromatin accessibility, and that artificial prolongation of L1 transcription in mouse embryos interferes with their development.…”
Section: A Possible Role For Misregulation Of Retrotransposon Expressmentioning
confidence: 99%
“…REs can serve as genes for long ncRNAs (Lu et al, 2014). L1s have a function similar to lncRNA in regulating the expression of genes necessary for self-renewal of stem cells and for preimplantation development (Honson, Macfarlan, 2018).…”
Section: The Relationship Of Transposable Elements With Non-coding Rnmentioning
confidence: 99%
“…Despite the lack of mitotic activity of mature neurons, the specific expression of TEs in them is important in controlling both interneuronal interactions and the structural and functional characteristics of neurons (Bailie et al, 2011;Richardson et al, 2014;Erwin et al, 2016). These properties may be due to processing from transcripts of transposons of specific long ncRNAs (Lu et al, 2014;Honson, Macfarlan, 2018) and microRNAs (Piriyapongsa et al, 2007;Yuan et al, 2010Yuan et al, , 2011Qin et al, 2015). Indeed, in experiments on laboratory animals, the enrichment of specific miRNAs in certain structures and regions of neurons was revealed.…”
Section: The Role Of Retroelements In Interactions Between Neuronsmentioning
confidence: 99%
“…In plants, transposon‐derived long non‐coding RNAs (TE‐lncRNAs) appear to be involved in stress responses (Wang et al, ) and root development (Cho & Paszkowski, ). In mammals, a LINE1 ‐derived lncRNA acts as a nuclear scaffold to modulate the expression profiles of crucial genes involved in ESC self‐renewal and pre‐implantation embryo development (Honson & Macfarlan, ; Percharde et al, ). Similarly, another TE‐lncRNA (human pluripotency‐associated transcript 5, HPAT5), derived from the endogenous retrovirus HUERS‐P1 and an Alu element, promotes pluripotency in pre‐implantation embryo development by functioning as a molecular sponge for let‐7 microRNAs (Durruthy‐Durruthy et al, ; Izsvák, Wang, Singh, Mager, & Hurst, ).…”
Section: Transposable Elements As Drivers Of Genome Plasticitymentioning
confidence: 99%